The Effect of Self-Management Education on Distress of Type 2 Diabetes Mellitus Patients in Ulin General Hospital Banjarmasin, South Kalimantan, Indonesia - Noor Diani; Maulidya Septiany; Lola Illona Elfani Kausar (Berkala Kedokteran, 2018)
Abstract: The purpose of this study was to analyze the effect of diabetes self management education (DSME) on distress of type 2 diabetes melitus patients which is hospitalized in Ulin General Hospital. This Study used Pre-Experiment with One Group Pretest-Posttest Design. The sample size was 32 patients. The results showed that the average of emotional burden before and after DSME was decrease, with difference number 0.325. The result of Distress among healthcare services before and after DSME was increase (0.211). The result of distress due to diabetes management before and after DSME was decrease (0.119). The result of distress interpersonal relationship before and after DSME was up (0,021). The analysis used Wilcox on Sign Rank test with p= 0,135 (p> 0,05) for emotional distress, p = 0,443 (p> 0,05) for Distress healthcare worker, p = 0.656 (p> 0.05) for distress due to diabetes management. P=0,527 (p>0,05) for Distress interpersonal relationship. The conclusion was there is no significant difference of distress level before and after DSME. It is shown that there is no effect of DSME on distress among patients with diabetes mellitus. Keywords: Diabetes Mellitus, Distress, Diabetes Self-Management Education (DSME)